Стан компенсації цукрового діабету у хворих у Тернопільській області - Пасєчко, Н. В.; Наумова, Л. В.; Мартинюк, Л. П. (Clinical Endocrinology and Endocrine Surgery, 2011)
The purpose of the study was to identify the level of haemoglobin A1c (HbA1c) in patients with diabetes mellitus in Ternopil region. There was not found relationship between stage of compensation and type of insulin used. The best compensation was found in women of childbearing age (30 years) who were motivated by a planned pregnancy and obtain an analogue of human insulin.The proportion of unsatisfactory compensation was significantly higher (64.7 %) as compare to satisfactory compensation (27.45 %) and good (7.8%) one in male diabetics. It was shown that average level of HgA1c is 10.2 % in Ternopil region. 4.65 % of patients are compensated, 15.11 % of diabetics are subcompensated and 80.83 % ones are decompensated.